2018
DOI: 10.5603/gp.a2018.0054
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nasal and oral flow of amniotic fluid in 46 non-anomalous fetuses with sonographic and echocardiographic examination

Abstract: Objectives: The aim of the paper was to assess nasal and oral amniotic fluid flows, with the use of color ultrasound and spectral Doppler, in normal fetuses. Material and methods:Forty-six fetuses of singleton gestations were studied prospectively. Spectrum imaging and maximal nasal fluid flow velocities were described. Episodes of regurgitation (external flow from the mouth), swallowing (internal flow at the level of oropharynx and then entrance to the esophagus) were evaluated in two groups: Fetuses < 27 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Irregular nasal fluid flows were observed more frequently in the fetuses that were < 27 weeks. In addition, both the mean maximal inspiratory fluid flow and mean maximal expiratory fluid flow were significantly higher in fetuses ≥ 27 weeks than in fetuses < 27 weeks of gestation [6].…”
Section: Introductionmentioning
confidence: 84%
“…Irregular nasal fluid flows were observed more frequently in the fetuses that were < 27 weeks. In addition, both the mean maximal inspiratory fluid flow and mean maximal expiratory fluid flow were significantly higher in fetuses ≥ 27 weeks than in fetuses < 27 weeks of gestation [6].…”
Section: Introductionmentioning
confidence: 84%
“…53,54 Further, at least one study has been reported that employs color and spectral Doppler in the vicinity of the fetal eye. 55 Shear wave elastography has been reported in the fetus, but not specifically in the fetal eye. 56…”
Section: Concepts Specific To Ophthalmic Ultrasoundmentioning
confidence: 99%